2021
DOI: 10.1038/s41598-021-88530-y
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of water bonding status of normal and psoriatic skin in vivo using diffuse reflectance spectroscopy

Abstract: Psoriasis affects more than 125 million people worldwide, and the diagnosis and treatment efficacy evaluation of the disease mainly rely on clinical assessments that could be subjective. Our previous study showed that the skin erythema level could be quantified using diffuse reflectance spectroscopy (DRS), and the hemoglobin concentration of most psoriatic lesion was higher than that of its adjacent uninvolved skin. While the compromised epidermal barrier function has been taken as the major cause of clinical … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Therefore, it is reasonable to interpret that the Corneometer readings had decent correlation to the PASI “thickness” and “desquamation” scores. On the other hand, the PWFR values gathered from the DRS system is an effective indicator of water-protein binding status in epidermis which directly reflects the skin barrier function 10 . Abnormal desquamation is a visible clinical manifestation of the disrupted skin barrier function.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, it is reasonable to interpret that the Corneometer readings had decent correlation to the PASI “thickness” and “desquamation” scores. On the other hand, the PWFR values gathered from the DRS system is an effective indicator of water-protein binding status in epidermis which directly reflects the skin barrier function 10 . Abnormal desquamation is a visible clinical manifestation of the disrupted skin barrier function.…”
Section: Resultsmentioning
confidence: 99%
“…In short, an ANN model was trained with diffuse reflectance computed from Monte Carlo simulations to determine the spectral information of tissue absorption and reduced scattering from the measured diffuse reflectance spectra. Specifically, the model was used to recover the skin absorption and reduced scattering spectra in the wavelength range from 500 to 1380 nm, from which we used a wavelength span of 500 nm to 600 nm to quantify the hemoglobin level of skin and another wavelength range from 1230 to 1380 nm to investigate the state of dermal water-protein binding state 7 , 10 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Water is located intra-as well as extracellularly in the SC and forms bonds of different strength (ranging from tightly bound to unbound water) 25 with ICL, keratin and NMF, depending on the SC depth 22 as well as age and other factors. [26][27][28] Several methods have been used to examine the psoriatic SC, like TEWL, corneometry, 'attenuated total reflectance-Fouriertransform infrared spectroscopy', 29,30 tape-stripping, 31 multiphoton CARS tomography, 32 optical coherence tomography, 33 diffuse reflectance spectroscopy, 34 scanning electron microscopy 35 and laser scanning microscopy. 36,37 Previous studies have revealed a less ordered SC structure regarding lipid organisation in psoriatic lesions, 10,36,38 which is thought to be partly due to differences in the composition of ceramides.…”
Section: Introductionmentioning
confidence: 99%
“…Several methods have been used to examine the psoriatic SC, like TEWL, corneometry, ‘attenuated total reflectance—Fourier‐transform infrared spectroscopy’, 29,30 tape‐stripping, 31 multiphoton CARS tomography, 32 optical coherence tomography, 33 diffuse reflectance spectroscopy, 34 scanning electron microscopy 35 and laser scanning microscopy 36,37 . Previous studies have revealed a less ordered SC structure regarding lipid organisation in psoriatic lesions, 10,36,38 which is thought to be partly due to differences in the composition of ceramides 38,39 .…”
Section: Introductionmentioning
confidence: 99%